Hubungan Motivasi Kerja, Efesiensi Kerja, dan Etos Kerja Terhadap Produktivitas Kerja Karyawan di Black Campaign Coffe Tangerang - Almara Hawa Sukmarani; Hani Hasanah; Muhammad Djaelani; Lely Syafawi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine the relationship between work motivation (X1), work efficiency (X2), and work ethic (X3), on employee productivity (Y) at Black Campaign Coffee Shop Tangerang. The population in this study were employees of the Black Campaign Coffee Shop Tangerang. The sample in this study was 50 respondents. The sampling technique used is Proportionate Stratified Random Sampling. The instrument in this study uses a questionnaire with a measurement technique is a Likert scale. The results of this study indicate that the independent variable of work motivation (X1) has a two-way test t-table value of 1.677, the results obtained from the comparison of the t-count > t table (5.160 > 1.677) which means that work motivation has a significant influence on work productivity. , in addition to the independent variable Work Efficiency (X2) has a value of t table two-way test of 1.677, the results obtained from the comparison of the value of t count > t table (5.096 > 1.677) which means Work Efficiency has a significant influence on Work Productivity, and the independent variable work ethic (X3) has a value of t count > t table (4,593 > 1,677) which means that work ethic has a significant effect on work productivity. And simultaneously work motivation, work efficiency, and work ethic positively and significantly affect work productivity. Obtained f arithmetic > f table (15.712 > 2.81) with a significance level of 0.000 < 0.05.